Tackling the wicked problem of health networks: the design of an evaluation framework. Issue 5 (5th May 2019) - Cunningham, Frances Clare; Ranmuthugala, Geetha; Westbrook, Johanna Irene; Braithwaite, Jeffrey
Abstract : Networks are everywhere. Health systems and public health settings are experimenting with multifarious forms. Governments and providers are heavily investing in networks with an expectation that they will facilitate the delivery of better services and improve health outcomes. Yet, we lack a suitable conceptual framework to evaluate the effectiveness and sustainability of clinical and health networks. This paper aims to present such a framework to assist with rigorous research and policy analysis. The framework was designed as part of a project to evaluate the effectiveness and sustainability of health networks. We drew on systematic reviews of the literature on networks and communities of practice in health care, and on theoretical and evidence-based studies of the evaluation of health and non-health networks. Using brainstorming and mind-mapping techniques in expert advisory group sessions, we assessed existing network evaluation frameworks and considered their application to extant health networks. Feedback from stakeholders in network studies that we conducted was incorporated. The framework encompasses network goals, characteristics and relationships at member, network and community levels, and then looks at network outcomes, taking into account intervening variables. Finally, the short-term, medium-term and long-term effectiveness of the network needs to be assessed. The framework provides an overarching contribution to network evaluation. It is sufficiently comprehensive to account for many theoretical and evidence-based contributions to the literature on how networks operate and is sufficiently flexible to assess different kinds of health networks across their life-cycle at community, network and member levels. We outline the merits and limitations of the framework and discuss how it might be further tested.